Network EuroLifestyle - an independent scientific network (Italian Journal of Public Health, 2009)
The Network EuroLifestyle aims to contribute to the improvement of the population health status in the European Union. The network will do so by adequately informing stakeholders and the inhabitants of the European Union about health effects and consequences of different lifestyles. For that purpose the network will identify and help to reduce lifestyle-related health inequalities. EuroLifestyle will prepare high impact communication to provide sound information of lifestyle issues so that stakeholders and the European population can make informed lifestyle choices.